2015
DOI: 10.1039/c5ra00578g
|View full text |Cite
|
Sign up to set email alerts
|

Purification of yellow phosphorus tail gas for the removal of PH3 on the spot with flower-shaped CuO/AC

Abstract: The process of PH 3 adsorption removal for purifying yellow phosphorus tail gas on the spot with flowershaped CuO was investigated in this study. Flower-shaped and irregular-shaped CuO/AC adsorbents were prepared by hydrothermal and impregnation methods, respectively. They can effectively remove PH 3 less than 1 mg m À3 and the purification efficiency is nearly 100% without fluctuation. However, the morphology of CuO on the adsorbent surface plays an important role in phosphine adsorption. The breakthrough ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In addition, the W 4f XPS spectrum of HPW@UiO-66 (4f 7/2 , 36.43 eV; 4f 5/2 , 38.60 eV) suffers a positive shifting of the binding energy compared to that of HPW (4f 7/2 , 36.1 eV; 4f 5/2 , 38.3 eV), which confirms the decrease in the electron density on HPW in the HPW@UiO-66 system and clearly indicates electron transfer between HPW and UiO-66. Figure d represents the deconvoluted P 2p spectra, and the framed peaks at 130.6 and 134.4 eV are ascribed to the P 0 and P 5+ states . Parts e–g of Figure show the comparative difference in the chemical behavior with changes in the binding energy, which reveals the well interaction between the parent UiO-66 and HPW.…”
Section: Structural Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the W 4f XPS spectrum of HPW@UiO-66 (4f 7/2 , 36.43 eV; 4f 5/2 , 38.60 eV) suffers a positive shifting of the binding energy compared to that of HPW (4f 7/2 , 36.1 eV; 4f 5/2 , 38.3 eV), which confirms the decrease in the electron density on HPW in the HPW@UiO-66 system and clearly indicates electron transfer between HPW and UiO-66. Figure d represents the deconvoluted P 2p spectra, and the framed peaks at 130.6 and 134.4 eV are ascribed to the P 0 and P 5+ states . Parts e–g of Figure show the comparative difference in the chemical behavior with changes in the binding energy, which reveals the well interaction between the parent UiO-66 and HPW.…”
Section: Structural Characterizationmentioning
confidence: 95%
“…Figure 3d represents the deconvoluted P 2p spectra, and the framed peaks at 130.6 and 134.4 eV are ascribed to the P 0 and P 5+ states. 53 Parts e−g of Figure 3 show the comparative difference in the chemical behavior with changes in the binding energy, which reveals the well interaction between the parent UiO-66 and HPW. Deconvoluted Zr 3d core−shell XPS analysis displays two humps positioned at 182.7 and 185.1 eV representing 3d 5/2 and 3d 3/2 spin states, as placed in Figure 3e.…”
Section: Chemical Composition (Xps and Icp-oes Analysis)mentioning
confidence: 99%
“…Li et al 13 also did some research about the adsorptive behaviors of phosphine on Y zeolite and ZSM-5 recently. Ren et al 14 reported that active carbon with CuO can efficiently remove PH 3 to less than 1 mg/m 3 and the purification efficiency is nearly 100% without fluctuation. Except for active carbon and molecular sieve, Ning et al 15 investigated the capability of Cu−Fe modified diatomite in adsorbing H 2 S and PH 3 simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it will cause serious adverse effects on human health and the environment when industrial gases are released without removal of PH 3 and H 2 S. PH 3 is one of the highly toxic gases, which might cause immediate death at a level of 50 ppm exposure according to the National Institute for Occupational Safety and Health (NIOSH) . Nevertheless, PH 3 is present in coal syngas, acetylene gas, and yellow phosphorus tail gas and widely used in various industrial processes and fields, such as phosphine fumigation, semiconductor industry, and electronic industry. H 2 S is a major toxic and malodorous gas emitted from industrial processes, primarily from extraction and refining of oil and natural gas, coal gasification, yellow phosphorus tail gas, and acetylene production. PH 3 and H 2 S often coexist in yellow phosphorus tail gas, coal syngas, and acetylene production, which usually contain dust. Therefore, it is desirable to remove them simultaneously from industrial gases.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of adsorption and catalytic oxidation to remove harmful gases are extensively studied. Al 2 O 3 , V 2 O 5 , active carbon, and TiO 2 are often used as support and loaded with metals such as Fe, Mo, Cu, Ag, and Na for removing PH 3 and H 2 S. ,, Although these methods can remove PH 3 and H 2 S efficiently, there are some substantial drawbacks associated with their practical applications, such as the specific temperature range, directionality problem, catalyst poisoning, and deactivation caused by coexisting gas or other substances. Particularly, the dust in industrial gas, such as yellow phosphorus tail gas and coal gas, makes it impossible or impracticable to remove PH 3 and H 2 S by conventional methods of adsorption and catalytic. Since comprehensive control is a growing trend in pollution treatment and gas purification, , the simultaneous removal of PH 3 , H 2 S, and dust is highly desired.…”
Section: Introductionmentioning
confidence: 99%